2007
DOI: 10.1007/s00204-007-0196-3
|View full text |Cite
|
Sign up to set email alerts
|

Strong mutagenic effects of diesel engine emissions using vegetable oil as fuel

Abstract: Diesel engine emissions (DEE) are classified as probably carcinogenic to humans. In recent years every effort was made to reduce DEE and their content of carcinogenic and mutagenic polycyclic aromatic compounds. Since 1995 we observed an appreciable reduction of mutagenicity of DEE driven by reformulated or newly designed fuels in several studies. Recently, the use of rapeseed oil as fuel for diesel engines is rapidly growing among German transportation businesses and agriculture due to economic reasons. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…There is conflicting evidence about the extent to which biodiesel fuel exhaust emissions present a lower risk to human health relative to petroleum-based diesel emissions (Swanson, Madden & Ghio, 2007). German studies have shown significantly increased mutagenic effects, by a factor of 10, of the particle extracts from rapeseed oil in comparison to fossil diesel fuel; and the gaseous phase caused even stronger mutagenicity (Bünger et al, 2007). Biodiesel (rapeseed oil methyl ester) has been shown to have four times higher cytotoxicity than conventional diesel under idling conditions, while no differences were observed for the transient state (Bünger et al, 2000).…”
Section: Clinical and Toxicological Studiesmentioning
confidence: 99%
“…There is conflicting evidence about the extent to which biodiesel fuel exhaust emissions present a lower risk to human health relative to petroleum-based diesel emissions (Swanson, Madden & Ghio, 2007). German studies have shown significantly increased mutagenic effects, by a factor of 10, of the particle extracts from rapeseed oil in comparison to fossil diesel fuel; and the gaseous phase caused even stronger mutagenicity (Bünger et al, 2007). Biodiesel (rapeseed oil methyl ester) has been shown to have four times higher cytotoxicity than conventional diesel under idling conditions, while no differences were observed for the transient state (Bünger et al, 2000).…”
Section: Clinical and Toxicological Studiesmentioning
confidence: 99%
“…On the other hand, some studies reported no difference between diesel and biodiesel exhaust or nearly the same mutagenic effects [89,90]. Moreover, some studies reported increase in the mutagenic effects with the use of biodiesel added to diesel [91][92][93][94]. It is important to highlight that the studies found high mutagenicity considering that the biodiesel mutagenicity was generally high or similar compared to diesel and in some other studies were comparing biodiesel to low sulfur diesel.…”
Section: Mutagenicity and Genotoxicity Assessmentsmentioning
confidence: 98%
“…However, there is a current need for the study of non-regulated emissions. Some studies on unregulated substances, such PAHs, nitro HPAs, carbonyl compounds (CC) and both vapor and par-ticulate of light aromatic hydrocarbons, showed a lower amount of mutagenic compounds being emitted when using biofuels [8]. However, there are some contradictory results [9], which point to the need for further studies of such substances.…”
Section: Comentioning
confidence: 99%
“…Of the fuels assessed, BTL and HVO show similar tailpipe emissions, while transesterified lipids perform differently, with higher N O x emissions. Increased N O x emissions have been related to adverse health effects [108] and transesterified lipid combustion is under investigation [108][109][110].…”
Section: Health and Safety Issuesmentioning
confidence: 99%